Edukasi Pernikahan Dini melalui Diskusi dan Media Sosial - Selvi Loviana; Ayu Wafiani (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2022)
This community service activity program aims to provide education related to early marriage. Given the many cases of early marriage and divorce in Indonesia, education is very important. This community service activity from home aims to provide education to teenagers regarding early marriage and its impact. It is hoped that this education will be able to provide understanding to young people. Early marriage education is very important considering the number of early marriages that occur due to promiscuity. With this educational video, we can add insight regarding early marriage and its impact.